Topics in electromagnetic waves : devices, effects, and applications - Behari, Jitendra (New Delhi : Anamaya Publishers, 2005)
Conference papers
Includes bibliographical references and index
Keywords: Electromagnetic waves; Electromagnetic devices -- India; Electromagnetism -- Physiological effect